(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article deals with the problem of preservation of archaic grammatical forms in the phraseology, the basic types of case forms obsolete noun in Ukrainian and Russian phraseology. Comparative study of phraseological units of Ukrainian and Russian languages made it possible to identify differences and similarities in the use of relict forms in the elements of two related languages.